How classroom design impacts for student learning comfort: Architect perspective on designing classrooms - Kurnia Widiastuti; Mohamad Joko Susilo; Hanifah Sausan Nurfinaputri (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study aimed to determine the factors that influence student learning comfort in the classroom and its distribution. This explorative study employed 772 students who were elementary school, junior high school, and senior high school students in several Muhammadiyah Yogyakarta schools. Data collection techniques using open questionnaires. The data analysis technique uses qualitative analysis which consists of three stages: open coding, axial coding, and selective coding. The results showed that the factors that influence learning comfort of students in the classroom include: air circulation, quietness, cleanliness, adequate & supportive facilities, and peer attendance. These five factors are among other factors that are grouped into two: 1) factors originating from the physical environment (of building & site themes and of indoor space themes); and 2) factors from within its occupants (of human themes). The theme that shows the highest influence comes from the physical conditions in the classroom, that is indoor space themes.